Analisis Kelayakan Usahatani Kopi Arabika di Desa Sudalarang - Aditya Nugroho; Asep Permadi Gumelar; Fitri Awaliyah (AGRITEKH (Jurnal Agribisnis dan Teknologi Pangan), 2023)
This study aims to analyze the general description of the cost structure, income, and analyze the feasibility of arabica coffee farming. The research method used was descriptive quantitative method with 30 farmers as respondents. The research results show the average total cost is Rp. 15,668,212/Ha/year, the average investment cost is Rp. 24,727,038/Ha/year, the average income for farmers is Rp. 32,065,088/Ha/year. Arabica coffee farming in Sudalarang Village is feasible and feasible to develop, because the NPV is positive which is Rp. 26, 661,511, the IRR is higer than the applicable discount rate which is 22.9%, the B/C ratio is higer than one which is 1.6, and the payback period is 5 years and 1 months.